Analysis of Speech-Sign Semantic Equivalence in Simultaneous Communication in Kenya - and Peter Oracha, Adoyo (2017)
Effective communication between teacher and pupil is a requisite factor for educational attainment. For the deaf, ineffective communication is a major problem especially when onset of profound deafness takes places at an early age before language is acquired. At school, the language of classroom communication not only affects the child’s development but also influences ability to learn other curriculum contents. Pointing out reasons for failure by deaf children to compete favorably with their hearing peers, Johnson et al (1989) has indicated that the central problem on deaf education is embedded in the lack of an appropriate language of classroom communication. For a long time education for the deaf was conducted through the oral approach. It was later realized that this oral approach did not avail curriculum content to the deaf learners. In the 1980’s Total Communication arose as one of the solutions. According to Adoyo (2004), Total Communication was misunderstood for Simultaneous Communication, a communication system in which speech and sign are produced at the same time (Lane, Hoffmister & Bahan, 1996). Although SC has been used in Kenya for all these years, it has not produced the predicated large-scale improvement. In this study, an attempt was made to establish the capacity of SC to enhance understanding and to facilitate information processing. The investigation was carried out through an examination of the extent to which the spoken and signed messages were equivalent in meaning. The research question was: To what extent do teachers of the deaf maintain one-one, sign to-voice ratio during Simultaneous Communication transmission and to what degree is the spoken and signed message equivalent semantically?